BODY DYSMORPHIC DISORDER IN PATIENTS WITH OBSESSIVE-COMPULSIVE DISORDER: PREVALENCE and CLINICAL CORRELATES - Conceicao Costa, Daniel Lucas; Assuncao, Melissa Chagas [UNESP]; Ferrao, Ygor Arzeno; Conrado, Luciana Archetti; Gonzalez, Christina Hajaj; Fontenelle, Leonardo Franklin; Fossaluza, Victor; Miguel, Euripedes Constantino; Torres, Albina Rodrigues [UNESP]; Shavitt, Roseli Gedanke (Wiley-Blackwell, 2012)
Background The prevalence, sociodemographic aspects, and clinical features of body dysmorphic disorder (BDD) in patients with obsessivecompulsive disorder (OCD) have been previously addressed in primarily relatively small samples. Methods We performed a cross-sectional demographic and clinical assessment of 901 OCD patients participating in the Brazilian Research Consortium on Obsessive-Compulsive Spectrum Disorders. We used the Structured Clinical Interview for DSM-IV Axis I Disorders; Yale-Brown Obsessive-Compulsive Scale; Dimensional Yale-Brown Obsessive-Compulsive Scale (DY-BOCS); Brown Assessment of Beliefs Scale; Clinical Global Impression Scale; and Beck Depression and Anxiety Inventories. Results The lifetime prevalence of BDD was 12.1%. The individuals with comorbid BDD (OCD-BDD; n = 109) were younger than were those without it. In addition, the proportions of single and unemployed patients were greater in the OCD-BDD group. This group of patients also showed higher rates of suicidal behaviors; mood, anxiety, and eating disorders; hypochondriasis; skin picking; Tourette syndrome; and symptoms of the sexual/religious, aggressive, and miscellaneous dimensions. Furthermore, OCD-BDD patients had an earlier onset of OC symptoms; greater severity of OCD, depression, and anxiety symptoms; and poorer insight. After logistic regression, the following features were associated with OCD-BDD: current age; age at OCD onset; severity of the miscellaneous DY-BOCS dimension; severity of depressive symptoms; and comorbid social phobia, dysthymia, anorexia nervosa, bulimia nervosa, and skin picking. Conclusions Because OCD patients might not inform clinicians about concerns regarding their appearance, it is essential to investigate symptoms of BDD, especially in young patients with early onset and comorbid social anxiety, chronic depression, skin picking, or eating disorders. Depression and Anxiety 29: 966-975, 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: obsessive-compulsive disorder; body dysmorphic disorder; comorbidity; epidemiology; anxiety disorders